Growth and Characterization of Benzimidazolium Salicylate: NLO Property from a Centrosymmetric Crystal. (29th October 2015) - Amudha, M.; Rajkumar, R.; Thayanithi, V.; Praveen Kumar, P.
Abstract : A new organic charge transfer molecular complex salt of benzimidazolium salicylate (BSL) single crystals was grown by the slow evaporation solution growth technique using methanol as a solvent at room temperature. The grown crystals were characterised by single crystal X-ray diffraction (XRD) which confirms that the crystal belongs to monoclinic system with the centrosymmetric space group P21 /c . The crystalline perfection of the grown crystal was analyzed by high resolution X-ray diffraction (HRXRD). The presence of various functional groups was identified by FTIR spectrum. UV-Vis spectral study reveals that the BSL crystal is optically transparent in the wavelength region 342 nm–1100 nm. Dielectric measurements of the crystal at various frequencies were also determined. The mechanical properties of the grown crystal were assessed using Vickers microhardness testing. Nonlinear optical property of the crystal was confirmed using Kurtz and Perry powder technique and the SHG efficiency of the BSL crystal is 0.7 times greater than that of the standard KDP crystal.